Carlos Moreno Loachamin: capstone - Loachamin, Carlos Moreno, artist (Colorado State University. Libraries, 2023)
The artist's statement: The body of work I have made in my four years at CSU has been a ramping evolution in the exploration of contemporary American mental health struggles, the notion of the sublime, and the beauty in such raw emotions as shame, guilt, and exhaustion. This evolution has primarily taken place through material exploration. Beginning with pen and ink on paper my freshman year, I have ventured into different media as I've painted, sculpted, and animated pieces which grew imbued with flashes of self-flagellation, exhaustion, and the buckling weight that follows when one holds onto torturing ideals for an excruciating amount of time.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing